MEDIA INFORMASI PEMBELAJARAN MATA KULIAH UMUM PRAKTIKUM PENGANTAR TEKNOLOGI INFORMASI - Ketut Gus Oka Ciptahadi (Jurnal Teknologi Informasi dan Komputer, 2021)
ABSTRACTThe success of the teaching and learning process in the classroom is influenced by the information media used by educators or lecturers in explaining the material, the more creative the educators or lecturers are in presenting the material, of course the students will be so enthusiastic about taking the lessons. In a research case study, namely at the STIKOM Bali Institute of Technology and Business, located in Renon, Denpasar, researchers and lecturers at the campus encountered problems. When teaching an Introduction to Information Technology Practicum. In the learning process, the lecturer is required to provide an explanation regarding the hardware on the computer with its functions and uses. To open a CPU takes a long time. Also in explaining the components in the CPU, not all students can see clearly because the components are small.Related to this problem, the researcher offers a solution by utilizing 3D animation based technology. Where this 3D animation technology provides a more realistic appearance. The second objective is as an information media for the introduction of computer hardware to students in following the Introduction to Information Technology Practicum course. The method in developing 3D animation uses Research and Development (R&D). The last stage is testing the animation product in the form of questionnaires. The results of the questionnaire test with 30 respondents, most of the percentage of answers was in the very good category between 80% to 100%. So it can be said that the results of the questionnaire test, which consists of aspects of information, modeling, coloring and animation are good.Keywords: Information Media, Animation, Research and developmentABSTRAKKesuksesan proses belajar mengajar di kelas dipengaruhi oleh media informasi yang digunakan tenaga pendidik atau dosen dalam menjelaskan materi, semakin kreatif tenaga pendidik atau dosen dalam menyajikan materi tentunya para siswa akan menjadi begitu antusias untuk mengikuti pelajaran. Pada studi kasus penelitian, yaitu di Institut Teknologi dan Bisnis STIKOM Bali, berlokasi di Renon, Denpasar, peneliti sekaligus dosen dikampus tersebut mendapatkan permasalahan. Ketika mengajar Praktikum Pengantar Teknologi Informasi. Didalam proses pembelajaranya dosen diwajibkan memberikan penjelasan terkait hardware pada komputer berseta fungsi dan kegunaannya. Untuk membuka sebuah CPU membutuhkan waktu lama. Juga dalam menjelaskan komponen didalam CPU tidak semua mahasiswa dapat melihat jelas dikarenakan komponen berukuran kecil.Terkait permasalahan tersebut, peneliti menawarkan solusi dengan memanfaatkan teknologi berbasis 3D animasi. Dimana teknologi 3D animasi ini memberikan tampilan yang lebih realistis. Tujuan kedua sebagai media informasi pengenalan hardware komputer kepada mahasiswa didalam mengikuti matakuliah Praktikum Pengantar Teknologi Informasi. Metode didalam pengembangan animasi 3D menggunakan Research and Development (R&D). Tahap terakhir melakukan pengujian produk animasi berupa pengujian kuisioner. Hasil pengujian Kusioner dengan 30 responden, sebagian besar persentase jawaban berada pada kategori sangat baik diatara 80% sampai dengan 100%. Jadi dapat dikatakan hasil pengujian kuisioner, yang terdiri dari aspek informasi, modeling, pewarnaan dan animasi sudah baik.Kata Kunci : Media Informasi, Animasi, Research and development.